G GreenMile Oct 2008 41 0 Apr 28, 2009 #1 Hi there! \(\displaystyle 6*7=30\) \(\displaystyle 7*5=24\) \(\displaystyle 4*9=24\) \(\displaystyle 8*5=?\) According to the first three relations find \(\displaystyle 8*5=?\). Thank you.

Hi there! \(\displaystyle 6*7=30\) \(\displaystyle 7*5=24\) \(\displaystyle 4*9=24\) \(\displaystyle 8*5=?\) According to the first three relations find \(\displaystyle 8*5=?\). Thank you.

ADARSH Aug 2008 726 286 India Apr 28, 2009 #2 (6-1)x(7-1)=30 (7-1)x(5-1)=24 (4-1)x(9-1)=24 x=multiplication

Jhevon Feb 2007 11,663 4,210 New York, USA Apr 28, 2009 #3 GreenMile said: Hi there! \(\displaystyle 6*7=30\) \(\displaystyle 7*5=24\) \(\displaystyle 4*9=24\) \(\displaystyle 8*5=?\) According to the first three relations find \(\displaystyle 8*5=?\). Thank you. Click to expand... here is the relation: \(\displaystyle a*b = (a - 1)(b - 1)\) EDIT: well geez, thanks a lot Adarsh. I left the problem unanswered so long, but you decided to answer right before i did

GreenMile said: Hi there! \(\displaystyle 6*7=30\) \(\displaystyle 7*5=24\) \(\displaystyle 4*9=24\) \(\displaystyle 8*5=?\) According to the first three relations find \(\displaystyle 8*5=?\). Thank you. Click to expand... here is the relation: \(\displaystyle a*b = (a - 1)(b - 1)\) EDIT: well geez, thanks a lot Adarsh. I left the problem unanswered so long, but you decided to answer right before i did